2023
DOI: 10.1039/d3ce00608e
|View full text |Cite
|
Sign up to set email alerts
|

Virtual assessment achieved two binary cocrystals based on a liquid and a solid pyridine derivative with modulated thermal stabilities

Abstract: The melting point of a liquid and a solid pyridine derivative has been modified using the cocrystal formation approach by combination with two carboxylic acids. Their crystal packings have been analyzed and correlated with their thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…This methodology was successfully applied in our group in a previous work. 40 All the structures were energy-minimized using the COMPASS II force field in Materials Studio. 53,54 Then, geometry optimizations were done using the density functional theory (DFT) with B3LYP/6-31G(+) theory level with the Gaussian09 software version D.01.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 4 more Smart Citations
“…This methodology was successfully applied in our group in a previous work. 40 All the structures were energy-minimized using the COMPASS II force field in Materials Studio. 53,54 Then, geometry optimizations were done using the density functional theory (DFT) with B3LYP/6-31G(+) theory level with the Gaussian09 software version D.01.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…40−42 The dihydrate structure connected the HACA molecules through masked synthons 43 of water clusters supported by acid•••amide interactions, 41,42 whereas the cocrystal contained 2-pyridone (Pdon), presenting Pdon•••acid and amide•••amide synthons. 40 However, previous studies performed in the group with coordination compounds suggested a tendency of the HACA molecules toward being ordered by amide•••amide patterns, leading to supramolecular chains or cycles depending on the synthetic conditions. 44−46 Therefore, in this work, we will evaluate the behavior of HACA when combined with bipyridine-type coformers benefiting from the well-known acid•••pyridine heterosynthon.…”
Section: ■ Introductionmentioning
confidence: 98%
See 3 more Smart Citations